THE ROLE OF THE PROSECUTOR'S INVESTIGATOR IN REVEALING CRIMINAL ACTS OF CORRUPTION - Hidayah Zharta Pasha, Muhammad Sultan; Juwita Arsawati, Ni Nyoman (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
This report is entitled The Role of Attorney Investigators in Exposing Corruption Crimes (Case Study at the Denpasar District Attorney's Office). The background for writing this report is due to the rampant cases of criminal acts of corruption that have occurred. The investigation process to uncover corruption crimes committed by Denpasar District Attorney investigators must be carried out in an appropriate manner based on the Criminal Procedure Code and Attorney General Regulation Number: PER-039/A/JA/10/2010 as amended and supplemented with the Attorney General's regulation Number: PER-017/A/JA/07/2014 Concerning Administrative and Technical Management of Cases of Special Crimes. Then the problem is formulated, namely how to implement the role of the Denpasar District Attorney investigator in uncovering criminal acts of corruption and whether the obstacles experienced by Denpasar District Attorney investigators and the method used in this study is an empirical legal method. Legal materials obtained from primary data and secondary data. The material will be analyzed by qualitative analysis and conclusions will be drawn by inductive way.